Русский костюм. С Древней Руси до наших дней - Каштанов Юрий Евгеньевич (История России, 2011)
Экземпляры: ф.14 (2012) / Инвентарный номер: 54674 / Цена: / Сис.шифр: 63.5(2) / Авт.знак: К 31 / ГРНТИ: 03.61.91 / ББК: 63.5(2)^VLBC/M